2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6609804
|View full text |Cite
|
Sign up to set email alerts
|

A bilayer representation of the human atria

Abstract: Abstract-Atrial fibrillation is the most commonly encountered clinical arrhythmia. Despite recent advances in treatment by catheter ablation, its origin is still incompletely understood and it may be difficult to treat. Computer modelling offers an attractive complement to experiment. Simulations of fibrillation, however, are computationally demanding since the phenomenon requires long periods of observation. Because the atria are thin walled structures, they are often modelled as surfaces. However, this may n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In such cases, variation of the surface elements thickness can also be considered wherein all elements are considered as 3D with an additional factor defining the thickness (35). This is similar to the linear coupling elements where a cross-sectional area was required.…”
Section: Varying the Thickness Of The Tissuementioning
confidence: 99%
“…In such cases, variation of the surface elements thickness can also be considered wherein all elements are considered as 3D with an additional factor defining the thickness (35). This is similar to the linear coupling elements where a cross-sectional area was required.…”
Section: Varying the Thickness Of The Tissuementioning
confidence: 99%
“…AF induces this type of structural remodeling, based on experimental findings from goats (Eckstein et al, 2011), while it was revealed that this dissociation increases AF stability (Gharaviri et al, 2012b, 2017; Verheule et al, 2013). A methodology for the creation of a bilayer model of human atria, using CT images, is proposed by Vigmond et al (2013), where the difference between RA and LA thickness, as well as the main anatomical structures and fiber orientation, is taken into account. The dual layer approach has also been adopted to examine the effectiveness of different radiofrequency ablation strategies (Bayer et al, 2016).…”
Section: Resultsmentioning
confidence: 99%